The role of the educational counselors in dealing with crises (Eurasian Journal of Humanities and Social Sciences, 2023)
This research aims to study the factors and variables that affect the ability of educational counselors to solve psychological crises for school students in Nineveh Governorate. The research sample consists of 307 educational counselors working in various schools in the governorate, where there were 23 educational counselors in primary schools, 131 educational counselors in middle schools, 67 in middle schools, and 86 in secondary schools for the academic year 220-2021.The descriptive approach was used, and the researcher prepared a questionnaire consisting of (62) items, which was later modified to consist of only 40 items. The questions were divided into four areas: (the ability to know and analyze crises (10) paragraphs. The ability to devise solutions and plan for types of crises (10) paragraphs. Possession of guiding skills in dealing with crises directly (10) paragraphs. The counselor’s link to the mechanisms of the relationship in dealing with crises (10) paragraphs, The questions were presented to the specialists, and their validity and reliability were ensured. The researcher used a number of statistical methods to achieve the objectives of the research, including standard deviations, averages, and the T-test to measure the difference between statistical parameters. The research showed that the ability to identify psychological crises in schools was modest and not that professional, and this is acceptable in the security and living situation experienced by the Iraqi society. There were no statistically significant differences for the counselors' gender, which is the same as the counselors' academic degree. The counselors' experience was one of the most statistically significant variables in this research